Molecular Modeling Study of the Genotoxicity of the Sudan I and Sudan II Azo Dyes and Their Metabolites - Bienstock, Rachelle J.; Perera, Lalith; Pasquinelli, Melissa A. (Frontiers in Chemistry, 2022)
Azo dyes are defined by the presence of a characteristic N=N group. Sudan I and Sudan II are synthetic azo dyes that have been used as coloring agents. Although animal toxicity studies suggest that Sudan dyes are mutagenic, their molecular mechanism of action is unknown, thus making it challenging to establish thresholds for tolerable daily intake or to understand how these molecules could be modified to ameliorate toxicity. In addition, dye metabolites, such as azobiphenyl and 4-aminobiphenyl, have been correlated with epigenetic alterations. We shed some light on the mechanisms of Sudan dye genotoxicity through a molecular modeling study of Sudan I and Sudan II dyes and two common metabolites interacting with DNA as adducts. The results suggest that all four adducts cause significant perturbations to the DNA helical conformation and structure; thus, it can be inferred that DNA repair and replication processes would be significantly impacted.